Circulating Muscle-specific miRNAs in Duchenne Muscular Dystrophy Patients - Xihua Li; Yuying Li; Lei Zhao; Duo Zhang; Xuan Yao; Huihui Zhang; Yu-cheng Wang; Xin-yi Wang; Hongfeng Xia; Jun Yan; Hao Ying (Elsevier, 2014)
Noninvasive biomarkers with diagnostic value and prognostic applications have long been desired to replace muscle biopsy for Duchenne muscular dystrophy (DMD) patients. Growing evidence indicates that circulating microRNAs are biomarkers to assess pathophysiological status. Here, we show that the serum levels of six muscle-specific miRNAs (miR-1/206/133/499/208a/208b, also known as myomiRs) were all elevated in DMD patients (P < 0.01). The receiver operating characteristic curves of circulating miR-206, miR-499, miR-208b, and miR-133 levels reflected strong separation between Becker's muscular dystrophy (BMD) and DMD patients (P < 0.05). miR-206, miR-499, and miR-208b levels were positively correlated with both age and type IIc muscle fiber content in DMD patients (2-6 years), indicating that they might represent the stage of disease as well as the process of regeneration. miR-499 and miR-208b levels were correlated with slow and fast fiber content and might reflect the ratio of slow to fast fibers in DMD patient (>6 years). Fibroblast growth factor, transforming growth factor-β, and tumor necrosis factor-α could affect the secretion of myomiRs, suggesting that circulating myomiRs might reflect the effects of cytokines and growth factors on degenerating and regenerating muscles. Collectively, our data indicated that circulating myomiRs could serve as promising biomarkers for DMD diagnosis and disease progression.